MENGOPTIMALKAN KEMAMPUAN BERPIKIR ANALISIS KONSEP TEKANAN PADA ZAT PADAT MELALUI MODEL SIKLUS BELAJAR DENGAN PENDEKATAN METAKOGNITIF - DARWATI KARTIKASARI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
This Classroom Action Research conducted in the subject of Pressure on Solids aims to optimize students' analytical thinking skills through a learning cycle model with a metacognitive approach. The ability to think analytically is the foundation that students must have in understanding physics concepts and using them to solve physics problems in everyday life. The first meeting learning activities in solving problems using metacognitive knowledge and cognitive skills obtained the achievement of students' analytical thinking skills of 66.25%. In the learning process, students' self-concepts also need to be developed, because the success of learning in the cognitive and psychomotor domains is influenced by the affective conditions of students. A good student self-concept can be formed when the teacher is optimistic in the learning process and in the thinking processes of the students. The learning outcomes of the first cycle led to the learning process at the third meeting with the achievement of analytical thinking skills of 74.9%. This means that the metacognitive approach is able to optimize the level of students' analytical thinking in understanding the relationship between the concepts of force, area and pressure, and helps students to construct knowledge independently. In the fourth meeting through metacognitive experience, students are expected to be able to think autonomously, namely: having the ability to understand problems, the ability to apply concepts, the ability to connect problems with formulas that might be used, and the skills to use mathematics as a tool to draw conclusions on the phenomena encountered. The results of the self-assessment questionnaire showed that 73% of students were able to follow the learning process well even though the teacher needed encouragement to generate confidence in their abilities. The implication is that the achievement of daily tests is 64.15% and 70% of class VIIIB students at MTs Al Fatah Banjarnegara have finished studying. Through the learning cycle model with a metaconitive approach, it produces a balance in learning activities in cognitive (69), affective (74) and psychomotor (76) aspects. This means that students are quite able to analyze arguments and provide explanations based on correct and rational perceptions. In addition, students also have good attitudes and skills in carrying out the learning process and investigating pressure experiments on solids. ABSTRAKPenelitian Tindakan Kelas yang dilaksanakan dalam materi Tekanan pada Zat Padat ini bertujuan untuk mengoptimalkan kemampuan berpikir analisis siswa melalui model siklus belajar dengan pendekatan metakognitif. Kemampuan berpikir analisis merupakan landasan yang harus dimiliki siswa dalam memahami konsep fisika dan memanfaatkannya untuk menyelesaikan persoalan fisika dalam kehidupan sehari-hari. Kegiatan belajar pertemuan pertama dalam memecahkan soal menggunakan pengetahuan metakognitif dan keterampilan kognitif diperoleh ketercapaian kemampuan berpikir analisis siswa 66,25%. Dalam proses belajar konsep diri siswa perlu pula dikembangkan, karena keberhasilan pembelajaran pada ranah kognitif dan psikomotor dipengaruhi oleh kondisi afektif siswa. Konsep diri siswa yang baik dapat terbentuk bila guru memiliki optimistis dalam proses pembelajaran dan proses berpikir yang dilakukan siswanya. Hasil belajar siklus pertama mengantarkan dalam proses belajar pertemuan ketiga dengan ketercapaian kemampuan berpikir analisis 74,9%. Artinya pendekatan metakognitif mampu mengoptimalkan tingkat berpikir analisis siswa dalam memahami hubungan antar konsep gaya, luas dan tekanan, dan membantu siswa untuk mengkonstruksi pengetahuan secara mandiri. Dalam pertemuan keempat melalui pengalaman metakognitif diharapkan siswa mampu berpikir secara otonom, yaitu: memiliki kemampuan memahami persoalan, kemampuan menerapkan konsep, kemampuan menghubungkan persoalan dengan formula yang mungkin akan digunakan, dan keterampilan menggunakan matematika sebagai alat untuk menarik kesimpulan atas fenomena yang dihadapi. Hasil angket penilaian diri terdapat 73% siswa mampu mengikuti proses pembelajaran dengan baik walaupun diperlukan dorongan guru untuk membangkitkan kepercayaan akan kemampuan dirinya. Implikasinya diperoleh ketercapaian ulangan harian 64,15% dan 70% siswa kelas VIIIB MTs Al Fatah Banjarnegara tuntas belajar. Melalui model siklus belajar dengan pendekatan metakonitif menghasilkan keseimbangan dalam aktivitas belajar aspek kognitif (69), afektif (74) dan psikomotorik (76). Artinya siswa cukup mampu menganalisa argumen dan memberikan penjelasan berdasarkan persepsi yang benar dan rasional. Selain itu siswa juga memiliki sikap dan keterampilan yang baik dalam melakukan proses pembelajaran dan penyelidikan percobaan tekanan pada zat padat.